Les savoirs locaux : entre connaissances et reconnaissance - Carole Barthélémy (VertigO)
Local knowledge are more and more requested for interdisciplinary research or exercises of nature management. With the example of water management in France, we can study the place conferred to empirical knowledge held by amateur fishermen and the way in which these knowledge participate or not to the acknowledgement of this social group. We can analyse through three steps, an historical prospect, an ethnographic investigation and an interdisciplinary question, the important role, in environmental policies, of knowledge.